(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
This study aims to model the effect on job satisfaction leadership style and organizationalbeliefs in a universe made up of 145 workers. To contrast the hypothesesa multiple regression equation was applied which results shown that the beliefs andleadership styles have an explanatory power of 31% on the general job satisfactionwhich is highly significant. Specifically the style culture of control beliefs has asignificantly negative influence on job satisfaction in general and the participativeleadership styles a positive and significant influence on job satisfaction in general.